Athletes at high altitude - Khodaee, M.; Grothe, H. L.; Seyfert, J. H.; VanBaak, K. (Sports Health: A Multidisciplinary Approach, 2016)
Athletes at different skill levels perform strenuous physical activity at high altitude for a variety of reasons. Multiple team and endurance events are held at high altitude and may place athletes at increased risk for developing acute high altitude illness (AHAI). Training at high altitude has been a routine part of preparation for some of the high level athletes for a long time. There is a general belief that altitude training improves athletic performance for competitive and recreational athletes. Evidence Acquisition: A review of relevant publications between 1980 and 2015 was completed using PubMed and Google Scholar. Study Design: Clinical review. Level of Evidence: Level 3. Results: AHAI is a relatively uncommon and potentially serious condition among travelers to altitudes above 2500 m. The broad term AHAI includes several syndromes such as acute mountain sickness (AMS), high altitude pulmonary edema (HAPE), and high altitude cerebral edema (HACE). Athletes may be at higher risk for developing AHAI due to faster ascent and more vigorous exertion compared with nonathletes. Evidence regarding the effects of altitude training on athletic performance is weak. The natural live high, train low altitude training strategy may provide the best protocol for enhancing endurance performance in elite and subelite athletes. High altitude sports are generally safe for recreational athletes, but they should be aware of their individual risks. Conclusion: Individualized and appropriate acclimatization is an essential component of injury and illness prevention.